Utilization of Kepok Banana Peel Using Fermentation Technology as Sheep Feed in Medan Tuntungan Sub District - hasnudi (Talenta Publisher Universitas Sumatera Utara, 2019)
The cost of feed is the highest expenditure on animal husbandry management. One solution to reduce the high cost of feed is by utilizing local feed ingredients or abundant horticulture waste. Waste from bananas namely banana peel can be used as small ruminant animal feed so that feed efficiency can be achieved both in terms of cost, nutrition and feed formulation. Abundant banana skin waste that has not been used optimally so that it is feared can cause environmental pollution. To prevent the accumulation of horticultural waste, one of which is by giving cattle as feed used in the dry season. The method used in the first community service program is to approach, interview and deepen problems and find solutions to problems later. Secondly, learning methods by using teaching media in the form of a book of community service activities and ways of fermented kepok banana peels, giving brochures or leaflets and demonstration using media aids and banners that attract farmers' interests. The results that have been achieved have shown that increasing farmers' knowledge and income related to fermentation technology as animal feed by utilizing agricultural waste